Combined use of Wild-Type HBV precore and high herum iron marker as a potential tool for the prediction of cirrhosis in chronic Hepatitis B infection - Chook, J.B.; Ngeow, Y.F.; Yap, S.F.; Tan, T.C.; Mohamed, R. (2011)
Hepatitis B virus (HBV) and high liver iron deposits have both been associated with the development of cirrhosis. Among HBV factors, genotype and mutations in the basal core promoter (BCP) and precore regions have been most frequently studied but the evidence for a positive association with cirrhosis has been inconsistent. In this study, sera from persons with chronic HBV infection with and without cirrhosis were used for whole HBV genome analysis and for the estimation of serum iron marker (serum iron or ferritin) levels. Single codon analysis showed that the precore wild-type, TGG (nt 1,895-1,897), gave the highest accuracy (77.5) for the identification of cirrhosis compared to other codons. When TGG was analyzed together with the precore start codon wild-type, ATG (nt 1,814-1,816), the accuracy was improved to 80.0 (odds ratio = 35.29; 95 confidence interval = 3.87-321.93; Phi = 0.629; P < 0.001). When the serum iron marker was included for analysis, it was clear that a combination of a precore wild-type and high serum iron marker gave a better accuracy (90.0) (odds ratio = 107.67; 95 confidence interval = 10.21-1,135.59; Phi = 0.804; P < 0.001) for the identification of cirrhosis than either biomarker alone. It appeared that a combined use of both these biomarkers might help to predict the development of cirrhosis in a person with chronic HBV infection, but longitudinal studies are required to test this hypothesis. J. Med. Virol. 83:594-601, 2011. (C) 2011 Wiley-Liss, Inc.